COMPARATIVE ANALYSIS OF COMPLEX INFORMATION SYSTEM TESTING METHODS (World Science, 2023)
This study delves into the realm of complex testing methods, which play a pivotal role in ensuring the functionality and integrity of information systems. It provides a comparative analysis of five primary testing methods: performance testing, automated testing, availability testing, usability testing, and security testing. The research underscores the challenges faced during the practical application of these methods and highlights the critical importance of experienced testers, effective communication, a stable testing environment, regular testing, and the utilization of appropriate tools to enhance security and automation. The fast-paced evolution of technology has resulted in increasingly complex information systems. As a result, the need for effective testing methods to maintain quality control has grown substantially. Complex testing may be necessitated by a multitude of factors, including intricate component dependencies, the integration of cutting-edge technologies, and stringent adherence to security and performance standards. In addition to these complexities, technology organizations encounter challenges such as limited resources, time constraints, and the rapid pace of technological change.